Why They Stay and Why They Leave: Stay Interviews With Registered Nurses to Hear What Matters the Most. (March 2023) - Snyder, Amy; Whiteman, Kimberly; DiCuccio, Marge; Swanson-Biearman, Brenda; Stephens, Kimberly
Abstract : Registered nurse retention is declining, with a national turnover rate in 2021 of 27%. After implementing a toolkit, nursing leaders in 1 organization completed 75 stay interviews with nurses in a cardiothoracic telemetry and a cardiothoracic surgical intensive care unit. Nurses reported that unit culture, team/peers, and scheduling were important in decisions to stay in their positions, but respondents considered leaving for salary, growth/development, and traveling opportunities. The stay interview process affords nurse leaders an opportunity to examine why nurses stay or leave and supports the development of targeted retention strategies.